THE EFFECT OF CAPITAL STRUCTURE AND LIQUIDITY ON COMPANY VALUE AT PT. MAYORA INDAH TBK - Iqri Ayu Andira (Scientia Integritas Utama, 2023)
This study aims to determine whether the capital structure and liquidity affect the firm value of the company PT. Mayora Indah Tbk which is listed on the Indonesia Stock Exchange in 2014 - 2021. Data collection uses secondary data obtained from published financial statements published by the Indonesia Stock Exchange using the saturated sampling technique. The results of this study have tested classical assumptions in the form of assumptions of normality, multicollinearity and heteroscedasticity. The method of data analysis used multiple linear regression techniques. The results showed that the hypothesis of the capital structure variable had no effect on firm value and the liquidity variable had a negative and significant effect on firm value.